Beyond “Epicondylitis”: Integrating Mechanotransduction and Health Literacy into the Management of Lateral Elbow Tendinopathy - Kądziołka, Witold; Borówka, Karolina; Górka, Piotr; Domagała, Szymon; Tymińska, Paulina; Frączek, Julia; Wiater, Zuzanna; Brankowska, Karolina; Jakubowska, Marta; Olejnik, Michał (Quality in Sport, 2026)
Background: Lateral elbow tendinopathy (LET) is a prevalent musculoskeletal disorder characterized by pain and functional impairment at the common extensor origin. This narrative review explores the critical paradigm shift from the historical inflammatory "epicondylitis" model to a modern mechanobiological framework. Objective: To synthesize current evidence-based perspectives on the pathophysiology, diagnosis, and management of LET, emphasizing the optimization of quality of care through active loading protocols. Evidence Synthesis: Pathophysiological understanding has evolved from an inflammatory model to one of tendinosis, characterized by angiofibroblastic hyperplasia and a failed healing response. Clinical diagnosis relies on provocative maneuvers and objective measures, specifically Pain-Free Grip Strength (PFGS) and the Patient-Rated Tennis Elbow Evaluation (PRTEE), to ensure diagnostic quality and monitor therapeutic efficacy. A critical appraisal of passive interventions, such as corticosteroid injections and NSAIDs, highlights their limitations and potential for long-term clinical failure. In contrast, mechanotransduction-driven active protocols—including isometric loading for acute analgesia and Heavy Slow Resistance (HSR) training for structural remodeling—represent the modern gold standard. Furthermore, the integration of a biopsychosocial framework and the enhancement of patient health literacy are essential for addressing nociplastic pain and ensuring sustainable functional reintegration. Conclusions: Effective management of LET requires a structured, criterion-based transition to active management, prioritizing therapeutic loading over passive symptom masking to maximize long-term musculoskeletal health and minimize recurrence.